Panychok T. Y. Adaptation of Anglicisms in modern German - Panychok T. Y. (Philological Treatises, 2020)
The article reviews the causes of Anglicisms borrowing in modern German language, ways of their revenues, borrowing methods and integration of lexicographic processing.